2010
DOI: 10.1093/jac/dkq106
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of synergistic activity of bovine lactoferricin with antibiotics in corneal infection

Abstract: Objectives: The objectives of this study were to determine whether a synergistic effect could be obtained in vitro between bovine lactoferricin (B-LFcin) and antibiotics against Pseudomonas aeruginosa and Staphylococcus aureus isolates from ocular infections, and to evaluate the use of B-LFcin as an adjunct to the antibiotic treatment of corneal infection in vivo.Methods: Chequerboard and time -kill assays were performed to investigate the combined effects of B-LFcin and conventional antibiotics, including cip… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
50
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 66 publications
(54 citation statements)
references
References 49 publications
3
50
0
Order By: Relevance
“…Recently, Oo et al [86] reported that two antibiotics (ciprofloxacin and ceftazidime) act synergistically with bLfcin against various strains of P. aeruginosa isolated from corneal infections in vitro. In mouse corneas, the addition of bLfcin as adjuvant enhanced the activity of ciprofloxacin, with 1.5 log reduction of bacterial growth compared with negative control, although the peptide alone had no significant effect.…”
Section: Ocular Infectionsmentioning
confidence: 99%
“…Recently, Oo et al [86] reported that two antibiotics (ciprofloxacin and ceftazidime) act synergistically with bLfcin against various strains of P. aeruginosa isolated from corneal infections in vitro. In mouse corneas, the addition of bLfcin as adjuvant enhanced the activity of ciprofloxacin, with 1.5 log reduction of bacterial growth compared with negative control, although the peptide alone had no significant effect.…”
Section: Ocular Infectionsmentioning
confidence: 99%
“…The chequerboard plates were inoculated with 10 6 c.f.u. ml 21 of S. aureus and incubated at 37 uC for 24 h. To evaluate the effect of the combination, the fractional inhibitory concentration (FIC) was calculated for each drug; then, the FIC index (FICI) was calculated as follows (Oo et al, 2010):…”
Section: Methodsmentioning
confidence: 99%
“…Furthermore, synergistic activity of bovine lactoferricin (11 amino acids) with antibiotics was demonstrated against multiresistant clinical isolates of Staphylococcus aureus and Pseudomonas aeruginosa in vitro and in a model of corneal infection in mice. Lactoferricin also had an anti-inflammatory effect in cornea, suggesting that it leads to a decrease of cytokines and mediators involved in inflammation (Oo et al, 2010). Hence, lactoferrin as well as its derived peptides could be potential adjuncts to conventional antibiotics in combating these pathogens, which also infect diabetic foot ulcers.…”
Section: Lactoferrin and Lactoferricins Are Able To Prevent The Formamentioning
confidence: 99%